Komposisi Jenis dan Indeks Keanekaragaman Ikan Kerapu (Serranidae) yang di Daratkan Pada Tempat Pelelangan Ikan Lewoleba - Lasmi, Lasmi (Jurnal Perikanan Unram, 2025)
Lembata Regency marine waters have a high level of biota diversity. The purpose of the study was to determine the species composition and diversity index of grouper (Serranidae). Data analysis was carried out by calculating the index value of species diversity, species evenness and species dominance. The results showed that the species composition landed at Lewoleba Fish Auction Site (TPI) was dominated by Cephalopholis boenak species at 10%, followed by Variola louti, Epinephelus ongus, Epinephelus fasciatus, and Cephalopholis miniata at 9%, then followed by Plectropomus leopardus, Epinephelus coeruleopunctatus, and Anyperodun leucogrammicus at 8%, followed by Plectropomus oligacanthus, Plectropomus areolatus, and Epinephelus macrospilos at 7%, followed by Cephalopholis sonnerati at 6%, and the last was Epinephelus undulosus at 3%. The diversity index (H') varied from 2.452 to 2.548. Based on the index value, the diversity index category is moderate (1 < H' < 3). The diversity index (E) varied from 0.956 to 0.993. Based on the index value, the evenness index category is high or evenly distributed. The dominance index (E) varies from 0.080 to 0.093. Based on the index value, the dominance index category is low or almost no dominance.